Round Up of the Top SMU Social Media Content in 2013 -- SMU Infographics - Singapore Management University (Institutional Knowledge at Singapore Management University, 2014)
The best of our social media posts in 2013, as decided by you! Find out what you liked, viewed, shared or commented on most in this infographic.